Efficacy of Antimicrobial Activity of Rhinacanthus Nasutus (Linn.) Leaves in Different Extractions - P.VISWESWARA RAO,; A.SIVANARAYANA GOUDU,; S.SASIKALA,; M.DHANANJAYA NAIDU, (International Journal of Pharma and Bio Sciences, 2010)
The in vitro antimicrobial activity of Rhinacanthus nasutus leaves was investigated against various strains of bacteria and fungi viz. Staphylococcus aureus, pseudomonas aeruginosa, Klebsiella pneumonia, Escherichia coli and Aspergillus niger by disc diffusion method. The Methanolic and ethyl acetate extract in a dose of 20 mg/ml showed significant activity against Staphylococcus aureus and Klebsiella pneumonia when compared with the standard antibiotic ciprofloxacin (10 µg /disc) and ampicillin (10 µg/disc) respectively. Chloroform extraction showed great significant result against A.niger.